Relationship Between Cognitive Appraisal of Control and Cardiac Vagal Regulation During an Unsupported Ski Crossing of Greenland - Trabucchi, Pietro; Savoldelli, Aldo; Mourot, Laurent; Vacher, Philippe; Pellegrini, Barbara; Schena, Federico (Frontiers in Physiology, 2022)
Purpose: The aim of the present study was to investigate the relationships between Perceived Control (PC) and Hear rate variability (HRV) during a 27-day expedition, during which an unsupported crossing was made from the west coast to the east coast of Greenland (across the Ice Sheet); and that therefore a high PC represents a favourable factor for recovery and stress management. Methods: Four subjects participated in the study. PC was measured on alternated days in the evening at the end of the day, using the Pearlin Mastery Scale; and the next day, upon waking, heart rate using a wrist heart rate monitor and a chest strap. Together with the PC, the perceived effort was measured through the CR-100 Borg scale and each subject was asked to indicate the most emotionally significant event of the day. Time and frequency domain indices for heart rate variability were calculated. Results: Several correlations were observed between PC and HRV indices. In particular two indices in the time domain, SDNN (rrm = 0.51) and RMSSD (rrm= 0.46), showed a significant and strong positive correlation . Conclusion: The existence of a positive correlation between PC and cardiac vagal regulation is of great interest to individuals immerged into extreme situations, because it can affect performance or prevents maladaptive states or injuries. To improve stress management, it could be convenient for members of extreme expeditions to adopt forms of cognitive training that modify their cognitive appraisal in order to raise their perception of control.